A look at Fa Tzang Chinese Temple in Capitol Shopping Center, Bacolod City - Enriquez, Ma. Ileana Ong
This is a descriptive study of Fa Tzang Chinese Temple in Bacolod City, Negros Occidental from its establishment to the present time. It aims to provide the reader with a general image of the temple regarding its history, physical character, the people, the religious, philosophical, and socio-cultural aspects and its functions.. A series of interviews with selected key informants were conducted in gathering firsthand information. The researcher utilized both the observation method and the participant-observation methodin collecting additional data. Photo documentation was also utilized. The study found out that establishment of Fa Tzang Chinese Temple grew out of the needs of the Chinese people living in San Sebastian Street, which used ot be the commercial Center of Bacolod City until the fire of 1955 destryed most of the establishment there, who at the tune were already worshiping Te Ya Kong in a small chapel in San Sebastian. Soon, it grew to small for the growing adherents/devotees that they initiated the building of a bigger temple in the new commercial center of Bacolod - Capitol Shopping Center. They solicited from the affluent members of the Chinese community and soon planning and construction was initiated and the temple was constructed 1971.